Optimalisasi Kepemimpinan Kepala Madrasah sebagai Administrator dalam Meningkatkan Kompetensi Pedagogik Guru - Nila Nabilatul Rizqiya; Zahrotur Roifah; Nur Efendi; Sulistyorini Sulistyorini (Institut Agama Islam Hidayatullah Batam, 2026)
This study aims to analyze the optimization of madrasah principals’ leadership as administrators in enhancing teachers’ pedagogical competencies. The method used is a Systematic Literature Review (SLR) with content analysis based on Miles and Huberman’s interactive model, examining 28 selected literature sources through inclusion-exclusion criteria from Google Scholar, Garuda, and Sinta databases (2019–2026), using Instructional Leadership Theory as the analytical foundation. The results indicate that madrasah principals play a strategic role in administrative management, program planning, organizing, implementation, and educational supervision. Optimization is achieved through needs-based teacher development programs, continuous academic supervision, and a collaborative work culture. This study also produces a conceptual model illustrating the influence pathway of madrasah principal leadership on teachers’ pedagogical competency through these three main mechanisms. Remaining challenges include managerial limitations, time constraints, and resistance to change.